1995
DOI: 10.1007/bf00928155
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of allicin, an active principle in garlic

Abstract: Garlic has been claimed to be effective against diseases, in the pathophysiology of which oxygen free radicals (OFRs) have been implicated. Effectiveness of garlic could be due to its ability to scavenge OFRs. However, its antioxidant activity is not known. We investigated the ability of allicin (active ingredient of garlic) contained in the commercial preparation Garlicin to scavenge hydroxyl radicals (.OH) using high pressure liquid chromatographic (HPLC) method. .OH was generated by photolysis of H2O2 (1.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
138
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(147 citation statements)
references
References 17 publications
7
138
0
2
Order By: Relevance
“…Administration of allicin with CP showed a significant decrease in the level of TBARS compared to rats treated with CP alone, a result which agrees with other reported data that demonstrated apparent decrease in TBARS after administration of allicin (Prasad et al, 1995;Li et al, 2010). This activity may be due to the ability of allicin to scavenge hydroxyl and peroxyl radicals and superoxide anion (Kim et al, 2001) and modulating LP (Saravanan & Prakash, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Administration of allicin with CP showed a significant decrease in the level of TBARS compared to rats treated with CP alone, a result which agrees with other reported data that demonstrated apparent decrease in TBARS after administration of allicin (Prasad et al, 1995;Li et al, 2010). This activity may be due to the ability of allicin to scavenge hydroxyl and peroxyl radicals and superoxide anion (Kim et al, 2001) and modulating LP (Saravanan & Prakash, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…A variety of biological effects of allicin are attributed both to its SH-modifying and antioxidant properties [8,9]. L L-cysteine of the antioxidant glutathione may also be a target of allicin [5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports (25)(26)(27) have indicated that allicin is the predominant active component that is responsible for the majority of the biological activities of garlic, including attenuating ischemic injury, lowering blood pressure and antiarrhythmic effects (6,28,29). The chemical structure of allicin is CH 2 =CH-CH 2 -S(O)-S-CH 2 -CH=CH 2 , and it has been has been manufactured synthetically and produced worldwide (18).…”
Section: Discussionmentioning
confidence: 99%